The Influence of Career Development, Compensation and Work Commitment on Employee Performance at the Haji Makassar Regional General Hospital UPT - Muh. Farid Dwi Saputra; Mujahid; Nurmadhani Fitri Suyuthi; Muliyadi Hamid; Mohammad Hatta Alwi; Abdul Samad A (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This research was conducted with the aim of; (1) examine and analyze the effect of career development (enrichment) on performance; (2) examine and analyze the effect of compensation on performance; (3) examine and analyze the effect of work commitment on the performance of UPT of Makassar Hajj Regional General Hospital. This study uses primary data using the sampling method, namely the census method through a survey of 84 employees as well as a sampl, the survey was conducted from April 2024 to May 2024. Data were analyzed using the SPSS 24 program. The results of this study indicate that: (1) Career Development (Enrichment) has a positive and significant effect on performance; (2) Compensation has a positive and significant effect on performance; and (3) work commitment has a positive and significant impact on the work of employees at the UPT of Makassar Hajj Regional General Hospital. This means that career development opportunities, structured training, fair treatment in a career, career information, promotion and receiving salary according to work quality standards, receiving incentives, receiving benefits, health insurance services, pension services and feeling comfortable spending time for the organization, happy to join the company, enjoy working and living in the company, find it hard to leave the company. These factors can encourage the achievement of employee performance which is useful for the development of the performance of the UPT of Makassar Hajj Regional General Hospital.